2014
DOI: 10.1111/bju.12516
|View full text |Cite
|
Sign up to set email alerts
|

Reflex fluorescence in situ hybridization assay for suspicious urinary cytology in patients with bladder cancer with negative surveillance cystoscopy

Abstract: Objective To assess the ability of reflex UroVysion fluorescence in situ hybridization (FISH) testing to predict recurrence and progression in non-muscle invasive bladder cancer (NMIBC) patients with suspicious cytology but negative cystoscopy. Patients and methods Patients on NMIBC surveillance were followed with office cystoscopy and urinary cytology every three-to-six months. Between March 2007 and February 2012, 500 consecutive patients with suspicious cytology underwent reflexive FISH analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 31 publications
0
15
0
1
Order By: Relevance
“…In terms of the predictive role of FISH, Kim et al [ 32 ] reported the predictive role of FISH in NMIBC patients with negative cystoscopy and suspicious cytology in which positive FISH was a significant predictor of Rec (HR 2.35; 95% CI 1.42–3.90, p = 0.001) in multivariable analysis and for Prog (HR 3.01; 95% CI, 1.10–8.21, p = 0.03) in univariable analysis. It has further been shown that the decision to omit bladder biopsy because of negative UroVysion in patients with atypical cytology and negative or equivocal cystoscopy was cost-effective and may allow reduction of unnecessary adverse events [ 33 ].…”
Section: Urinary Biomarkers For the Surveillance Of Bladder Cancer Pamentioning
confidence: 99%
“…In terms of the predictive role of FISH, Kim et al [ 32 ] reported the predictive role of FISH in NMIBC patients with negative cystoscopy and suspicious cytology in which positive FISH was a significant predictor of Rec (HR 2.35; 95% CI 1.42–3.90, p = 0.001) in multivariable analysis and for Prog (HR 3.01; 95% CI, 1.10–8.21, p = 0.03) in univariable analysis. It has further been shown that the decision to omit bladder biopsy because of negative UroVysion in patients with atypical cytology and negative or equivocal cystoscopy was cost-effective and may allow reduction of unnecessary adverse events [ 33 ].…”
Section: Urinary Biomarkers For the Surveillance Of Bladder Cancer Pamentioning
confidence: 99%
“…25 However, due to the lack of data, even this recommendation is based on expert opinion rather than on evidence. We specifically excluded the other equivocal diagnostic category, "suspicious for malignancy," from this analysis, since it has been recently addressed 26 and in our experience and in the experience of others, 27 patients with this diagnosis are managed similarly to those with a diagnosis of "positive for malignancy/urothelial carcinoma." We specifically excluded the other equivocal diagnostic category, "suspicious for malignancy," from this analysis, since it has been recently addressed 26 and in our experience and in the experience of others, 27 patients with this diagnosis are managed similarly to those with a diagnosis of "positive for malignancy/urothelial carcinoma."…”
mentioning
confidence: 99%
“…25 To address the issue of the value of U-FISH testing in patients with equivocal urine cytology results, we performed a retrospective review of our experience with the U-FISH test performed in patients with AUC diagnosed on UTCy specimens, with the aim to determine its performance characteristics and its value in the risk stratification of the patients. We specifically excluded the other equivocal diagnostic category, "suspicious for malignancy," from this analysis, since it has been recently addressed 26 and in our experience and in the experience of others, 27 patients with this diagnosis are managed similarly to those with a diagnosis of "positive for malignancy/urothelial carcinoma." Secondary aims of this study were to determine if the performance of the U-FISH test improves with longer follow-up intervals due to the "anticipatory positive" results of the test, if alternative cutoff points for positivity would improve its performance, and if the performance of the test varies according to the type of specimen used (voided versus instrumented urine), age and sex of the patient, and indication for urine cytology (surveillance for UC or other indications).…”
mentioning
confidence: 99%
“…However, fluorescence in situ hybridization (FISH) techniques that detect aneuploidy of certain chromosomes in cells voided from the bladder characterizing them as malignant [ 47 ] can be used to detect so called molecular recurrence and has been used to risk stratify patients undergoing BCG therapy based on FISH results at early time points [ 45 , 46 ]. Notably, reflex use of FISH in the setting of suspicious cytology has not yet been shown to modify surveillance strategies [ 48 ].…”
Section: Consensus Recomendationsmentioning
confidence: 99%